CP-079 Chronic myeloid leukaemia and medication adherence with imatinib. Is there a cut off?. (14th February 2016) - Santoleri, F; Lasala, R; Ranucci, E; Costantini, A
Abstract : Background: In 2001, the introduction of imatinib in the USA and Europe deeply modified both the treatment of chronic myeloid leukaemia (CML) and the prognosis of patients. The scientific literature shows that imatinib is highly effective, with better rates for complete haematological response (CHR), and major and complete cytogenetic response (MCyR, CCyR). As is well known, strict adherence to therapy increases the percentage of clinical success. Purpose: We carried out a retrospective observational study aimed at evaluating medication adherence using the the ratio between received daily dose and prescribed daily dose (RDD/PDD) as the method for analysis of home therapy with imatinib in patients with CML. The correlation between adherence and clinical outcomes was investigated. Material and methods: This study was carried out in the pharmacy unit and haematology unit of Pescara Hospital. The analysis included data collected by pharmacists and haematologists in the period between 1 January 2007 and 31 March 2015. All CML patients treated with imatinib were included in the study. Data were recorded in a specific online database, Pharmadd.it., created ad hoc by hospital pharmacists. The method used to calculate medication adherence was the ratio between RDD/PDD. Statistical analysis of the collected data was performed with a Studio v.0.98.1103, running R v.3.1.3. Results: 53 patients were enrolled in the first year and 50 patients were enrolled in the second year. We observed the level of adherence for each of the following groups of answers for the first and second years: complete answer (adherence 0.96, 0.95), MR4.5 (adherence 1.00; no patients with MR4.5 in the second year), MR4 (adherence 0.93, 0.91), MR (adherence 0.96, 0.97), warning (adherence 0.91, 0.89) and failed (adherence 0.79, 0.84). Conclusion: The results showed that the higher the adherence, the lower the level of BCR-ABL. Furthermore, the outcome for cut offs ≥0.9 were significantly higher than cut offs <0.90. References and/or Acknowledgements: Santoleri F, Sorice P, Lasala R, et al . Patient adherence and persistence with imatinib, nilotinib, dasatinib in clinical practice. PLoS One 2013;8(2) No conflict of interest.